Optimalisasi Pengembangan Produksi Kerajinan Eceng Gondok dan Pemasaran Berbasis Media Sosial UMKM Alata Hande Gorontalo - Rustam, Suhardi; Lomagio, Afriana; Mooduto, Sarlis; Patilima, Vina Saputri; Paramata, Faldimas; Ramansyah, Ramansyah (Abdimas Universal, 2026)
This community service program aims to empower a group of housewives in Alata Village, Gorontalo, through optimizing the production and marketing of water hyacinth handicrafts. Alata Hande Made MSMEs, as existing artisan partners, face challenges in production scalability and limited marketing reach. The main problems identified are the lack of technical production skills in housewives and the lack of utilization of digital marketing to reach a wider market. The solutions offered include intensive technical training on the entire production process, from raw material processing to finished products, as well as digital marketing training that includes the use of social media, product photography, and simple financial recording. The method of implementation of this program uses a participatory approach that is divided into five stages: socialization, training, technology implementation, mentoring, and evaluation. The implementation of appropriate technologies such as portable drying racks and digital templates for the calculation of the cost of production (COGS) is also carried out to improve efficiency. This Program is expected to increase the skills and economic income of partner families, create competitive local product brands, and support the sustainable use of Natural Resources in line with the Sustainable Development Goals (SDGs).